النمذجة القياسية لتأثير حجم الودائع على حجم القروض في البنوك التجارية دراسة حالة بنك ناتيكسيس وكالة عنابة خلال الفترة ) 2011-2020 - - شيماء شرفي (My University, 2022)
This study aimed to answer the problem related to the impact of the volume of deposits on loans to commercial banks through a standard model ͵ by relying on the descriptive approach in the theoretical aspect by describing the study details accurately and in depth in the subject such as describing the volume of deposits with commercial banks..., as well as the study approach The case in the practical side by displaying the time series of the evolution of the volume of depo(2011-2020)͵ and highlighting the effect of the volume of deposits on the volume of loans to these banks based on several tests, including stability test, ACF correlation function test And PACF, ADF and co-integration test (causality test), as well as standard modeling of the effect of deposit volume on loan volume, based on simple regression method. Our study concluded by measuring the extent of the impact of the size of deposits on the lending capacity of commercial banks. It has shown us the critical importance of the amount of money they own in the form of deposits and deal with them in the form of loans directed towards huge investments that serve the economy. As for the standard model, it is the model that helped us analyze The independent variable (X: deposits) and the dependent variable (Y: loans) and knowing the effect of the independent variable on the dependent variable based on the simple regression method and the SPSS program (E-views). ..................................................... هدفت هذه الد ا رسة للإجابة عن الإشكالية المرتبطة بالتأثير حجم الودائع على القروض للبنوك وذلك من خلال الاعتماد على المنهج الوصفي في الجانب النظري ͵ التجارية من خلال نموذج قياسي بوصف جزئيات الد ا رسة بدقة و التعمق في الموضوع كالوصف حجم الودائع لدى البنوك التجارية...، وكذا منهج د ا رسة الحالة في الجانب التطبيقي بالعرض السلاسل الزمنية لتطور حجم الودائع و حجم و إب ا رز تأثير حجم ͵) 2020- خلال السنوات ) 2011 ( Natixis Banque) القروض لدي بنك الودائع على حجم القروض لهذه البنوك بالاعتماد على عدة اختبا ا رت من بينها اختبار الاستق ا ررية، و اختبار التكامل المشترك ) اختبار السببية (، وكذا ADF ،PACF و ACF اختبار دالة الارتباط النمذجة القياسية لتأثير حجم الودائع على حجم القروض و بالاعتماد على أسلوب الانحدار البسيط. خلصت د ا رستنا في قياس مدى تأثير حجم الودائع على القدرة الاق ا رضية للبنوك التجارية و قد تبين لنا الأهمية البالغة لحجم الأموال التي تمتلكها في شكل ودائع و تتعامل بها في شكل قروض موجهة أما فيما يتعلق بالنموذج القياسي فهو النموذج الذي ساعدنا في ͵ نحو استثما ا رت ضخمة تخدم الاقتصاد تحليل المتغير المستقل )الودائع( و المتغير التابع )القروض ( و معرفة تأثير المتغير المستقل على .SPSS ( E-views) المتغير التابع بالاعتماد على أسلوب الانحدار البسيط و على برنا